2018
DOI: 10.1108/jrme-11-2016-0048
|View full text |Cite
|
Sign up to set email alerts
|

Using the business model canvas to improve investment processes

Abstract: Purpose-This paper investigates how entrepreneurs market their business opportunities towards business angels in the investment process. This is achieved by introducing the Business Model Canvas as a mitigating framework to help entrepreneurs in communicating and structuring the information desired by business angels. Design/methodology/approach-This paper mobilises a case study approach by following a series of investment processes and investment meetings between entrepreneurs and business angels through 27 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 52 publications
0
23
0
3
Order By: Relevance
“…Methodology will be discussed further below. Sort et al (2018), in the article "Using the business model canvas to improve investment processes," focused more on communication performance than on financial or survival performance. The authors' interviews revealed that the BMC was a good framework for providing a shared language between entrepreneurs and angel investors.…”
mentioning
confidence: 99%
“…Methodology will be discussed further below. Sort et al (2018), in the article "Using the business model canvas to improve investment processes," focused more on communication performance than on financial or survival performance. The authors' interviews revealed that the BMC was a good framework for providing a shared language between entrepreneurs and angel investors.…”
mentioning
confidence: 99%
“…[45] A new business opportunity may lead firms to subsequent innovation and yield future profitability, but there is obvious uncertainty because the degree of novelty differs greatly among firms and industries. [46] Under this uncertainty, while VC investment has become an increasingly important source of financing for startups and small and mid-sized companies [45,[47][48][49], it is not easy for companies to achieve investments. Companies that like to achieve financial investments often rely on their own business knowledge to market their potential business opportunities.…”
Section: B Emerging Business Opportunitiesmentioning
confidence: 99%
“…Companies that like to achieve financial investments often rely on their own business knowledge to market their potential business opportunities. [45] There are clear differences between business ideas and business opportunities. While business ideas are difficult to share with others because it is often subjective and abstract [50,51], business opportunities are more conceptualized in terms of product or service including target markets.…”
Section: B Emerging Business Opportunitiesmentioning
confidence: 99%
“…Essa forma de enxergar o mundo é sustentada pela visão sistêmica que representa um recurso fundamental para o empreendedor, uma forma de mudar do pensamento linear para o holístico e sistêmico. Para tal, a utilização de conceitos, métodos e ferramentas se tornam essenciais aos empreendedores por contribuírem para seu desenvolvimento bem como para a compreensão de estruturas e atividades (Osterwalder & Pigneur, 2011;Kozlowski, Searcy & Bardecki, 2018;Sort & Nielsen, 2018 (Teixeira, 2018).…”
Section: Ferramenta Canvasunclassified